Helicopter Money and Basic Income, or a Work-Based Society? A Brief History of Wages, Benefi ts, Loans and Quantitative Easing - Vargha, Bálint Tamás (Public Finance Quarterly, 2022)
Following the coronavirus outbreak, and especially before infl ation became a key factor in this period, several crisis management proposals raised the possibility of a universal basic income, which could be backed by the central bank’s money creation. Th e following paper is an essay that seeks to grasp the political economic meaning and implications of the propositions related to helicopter money and basic income. We cannot avoid observing the essence of these proposals, presented fundamentally as a distribution-related issue, in the historical context of value, work and money creation. Helicopter money appears in this light as a new paradigm of extensive growth, which at fi rst glance comes off as a fi nancial innovation, but paradoxically rather bears a relationship with a pre-capitalist conception of value. Moreover, helicopter money is a wage-substitute transfer that does not respond to the social and symbolic void that has replaced work. It appears to be a welfare instrument, while it can only rest on the separation of production and consumption on a global scale. Helicopter money is an extension of quantitative easing by other means, which unveils the motives for money creation. It is an overture to the thought experiments of ‘value without work’ and ‘economy without people’.